EXPERIMENTAL PREDICTION OF THERMAL CONDUCTIVITY OF ETHYLENE GLYCOL SILVER BASED NANOFLUID - AZMI, MUHAMMAD MERQHA’EL (2018)
This report discussed on the preparation and the characterization of the nanofluids for the thermal characterization application. The purposes of this project are to formulate a stable nanofluid, experimentally analyzed the thermal conductivity of the nanofluids and derive equations from data collected. Scopes of study focused in this report are the nanoparticles, base fluids, and the volume percentage of the particles inside nanofluids. The nanoparticles selected for this project is silver nanoparticles of different size which are 20nm and 50nm while the base fluids is Ethylene Glycol. The nanofluids are prepared using two-step method whereby the process of synthesizing the nanoparticles are separated from mixing with base fluids. The nanofluids are formulated with different volume percentage of nanoparticles which are 0.3%, 0.5% and 1.0%. The thermal conductivity of the nanofluids is measured using KD2 Pro portable thermal analyzer. Result obtained shows that presence of nanoparticles inside base fluids can enhance the thermal conductivity compared to base fluids. The thermal conductivity of nanofluids is increasing with the temperature and decreasing with the size of nanoparticles. Nanofluids with 50 nm particles exhibit a better thermal conductivity compared to nanofluids with 20 nm particles. Equations derived from the graph constructed from the data obtained can be used to calculate the thermal conductivity of the nanofluids at different temperature and volume concentrations.